Iraq-Technical Assistance Report-Customs Valuation, Rules of Origin and Tariff Classification of Goods. (IMF Staff Country Reports; Country Report ;, 2021)
This report summarizes key findings and recommendations from a remote technical assistance (TA) assignment performed by a short-term expert (STX), Mr. Djamel Bouhabel, from January 17 to February 4, 2021, to the General Customs Authority of Iraq (GCA). The main objective of the TA was to advise GCA on the development and effective application of customs assessment processes based on international standards and best practices.